The Influence of Internal and External Factors on Investment Decisions with Financial Literature as Moderate Variables - Hartini, Luh Putu Yuni; Suarmanayasa, I Nengah; Sinarwati, Ni Kadek (International Journal of Social Science and Business, 2022)
Investment is one way to develop the funds owned, and at a particular time, the funds generated can provide benefits according to the expectations of the investment objectives. The purpose of investment is to obtain compensation from the amount of money invested in a certain period, except for inflation, as well as due to uncertainty in future payments. This study aims to analyze the influence of risk profile, diversification behavior, retirement preparedness on investment decisions, external factors consisting of regulation and information technology on investment decisions and investigate the effect of risk profile, diversification behavior, retirement preparedness, regulation, and technology. This study uses a quantitative approach; the research population is Bank Mandiri Third Party Fund (DPK) customers in Bali Province with a sample of 100 customers using a simple random sampling technique. Data was collected using a questionnaire distributed via a google form. The data analysis technique used Multiple Regression Analysis with SPSS for Windows version 2.1 program. The results showed that internal factors consisting of a risk profile had a negative and insignificant effect. Diversification behavior and Retirement preparedness had a positive and insignificant impact on investment decisions; external factors consisting of regulation and information technology had a positive and significant effect on investment decisions. And financial literacy cannot moderate risk profile and diversification behavior towards investment decisions. In contrast, financial literacy can mediate retirement preparedness, regulation, and information technology on investment decisions.